Judicial Considerations Regarding Criminal Sentences Involving Community Service Under The National Criminal Code - Ilham Shofil Fuadi; Sanusi Sanusi; Gunadi Rasta (Interdisciplinary Social Studies, 2026)
This study examines the implementation of Article 85 paragraph (2) of the Indonesian Criminal Code in judicial decisions concerning social work punishment. The background of this research is rooted in the paradigm shift of Indonesian criminal law from retributive justice toward rehabilitative and restorative justice, particularly through the introduction of social work punishment as an alternative to imprisonment. The objective of this study is to analyze the extent to which judges internalize the normative parameters stipulated in Article 85 paragraph (2) in their legal considerations. This research employed a normative legal method supported by a case approach, analyzing three court decisions and complemented by limited interviews with legal practitioners. The results indicate that judicial consideration in Decision Number 1/Pid.C/2026/PN Mbn and Decision Number 4/Pid.C/2026/PN Ksp remains partial, as judges only consider limited factors such as confession and ability to pay fines, while other mandatory elements are not explicitly analyzed. In contrast, Decision Number 78/Pid.B/2025/PN Pps demonstrates a more comprehensive application of the normative parameters. The discussion reveals inconsistencies in the internalization of criminal individualization principles, which may affect sentencing quality and legal certainty. In conclusion, judges have not fully and systematically applied Article 85 paragraph (2), highlighting the need for stronger interpretative consistency, clearer technical guidelines, and improved institutional support to ensure the effective implementation of social work punishment within the Indonesian criminal justice system.